2D Ultrawide Bandgap Semiconductors: Odyssey and Challenges. Issue 4 (11th March 2022) - Yang, Wen; Xin, Kaiyao; Yang, Juehan; Xu, Qun; Shan, Chongxin; Wei, Zhongming
Abstract: 2D ultrawide bandgap (UWBG) semiconductors have aroused increasing interest in the field of high‐power transparent electronic devices, deep‐ultraviolet photodetectors, flexible electronic skins, and energy‐efficient displays, owing to their intriguing physical properties. Compared with dominant narrow bandgap semiconductor material families, 2D UWBG semiconductors are less investigated but stand out because of their propensity for high optical transparency, tunable electrical conductivity, high mobility, and ultrahigh gate dielectrics. At the current stage of research, the most intensively investigated 2D UWBG semiconductors are metal oxides, metal chalcogenides, metal halides, and metal nitrides. This paper provides an up‐to‐date review of recent research progress on new 2D UWBG semiconductor materials and novel physical properties. The widespread applications, i.e., transistors, photodetector, touch screen, and inverter are summarized, which employ 2D UWBG semiconductors as either a passive or active layer. Finally, the existing challenges and opportunities of the enticing class of 2D UWBG semiconductors are highlighted. Abstract : The increasing interest in 2D ultrawide bandgap materials requires in‐depth research on their crystal structures, physical properties, preparation, and potential applications. In this review, comprehensive progress of 2D ultrawide bandgap semiconductor materials is discussed. Proposed challenges need to be addressed in the future to unveil their potential applications.